Failure of Securitizing the Climate Change Issue at the United Nations Security Council (2007-2019) - Murni Kemala Dewi (Department of International Relations, Universitas Andalas, 2020)
Abstract This paper describes the dynamics of debates on the securitization of climate change issue at the United Nations Security Council (UNSC), which took place from 2007 to 2019. Although there have been four open debates on this issue at the UNSC, until 2019, the process of the securitization of climate change issue has failed. Prior studies discussing the same concern has only explained some of the reasons proposed in the debates, such as relating to the mandate of the UNSC, the division of work in the UN units, and whether the issue of climate change could be considered as a security issue. By applying the Externalist School of Securitization theory, this paper analyzes the relationship between sociolinguistics and socio-politics in the dynamics of the debates on the securitization of climate change issue at the UNSC and the roles of the permanent members in the debates. The main argument in this research is spotted on the existing rejection against the framing of climate change as a security issue by several UNSC permanent members, hence no mitigation policy can be mutually agreed upon. This has resulted in a failure in the process of securitizing the climate change issue at the UNSC (2007-2019). Keywords:The Security Council, Climate Change, Securitization